The Impact of Graft Nephrectomy on Subsequent Transplants: Multivariate Analysis of Risk Factors for Second Graft Loss and for Multiple Transplantations–A Single-Center Retrospective Study. (16th September 2013) - Giorgakis, Emmanouil; Syed, Asim; Gonzalez, Hector
Abstract : Introduction . The management of a failed primary allograft remains unclear and the evidence of the effect of transplantectomy to future transplants conflicting. Aim of this study is to review the impact of failed primary graft nephrectomy on future transplants. Materials/Methods . Retrospective study of 101 patients retransplanted in a single institution. Median follow-up was 68 months. Patients were divided into two groups; G1 (n = 49 ) was the nephrectomy group; G2 (n = 52 ) was the graft in situ group. The patients' and second graft survival were analysed with the Kaplan-Meier method. The patients' and transplant characteristics were analyzed with student's t -test. The retransplant risk factors and the risk factors for multiple transplants were obtained via a logistic regression model. Results . The odds of second graft loss post-transplantectomy were high (OR = 5.24). Demographics, HLA mismatch and first graft rejection rates were similar among the two groups and did not affect the outcome. Transplantectomy accelerated the loss of a future failing graft. Multivariate analysis showed transplantectomy as independent risk factor for second allograft loss. Transplantectomy and younger age are significant independent risk factors for future multiple transplants. Conclusion . Transplantectomy of the failed primary graft is an independent risk factor for retransplant loss and for multiple renal transplants.